Review about the use of the Invertebrates in Pisciculture: Termites, Earthworms and Maggot - VODOUNNOU, D.S.J.V.; DJISSOU, Arnauld Sedjro Martin; KPOGUE, D.N.S.; Dakpogan, H.; MENSAH, GUY APOLLINAIRE; FIOGBE, EMILE DIDIER (My University, 2015)
The halieutic products have a very significant role in human nutrition. They constitute the most significant animal protein nutrient source for Beninese population. But, the offer of the national production is low compared to the demand population. The problem of the aquaculture is the feed. This is not well justified by ashormentionned points. The object of the study is to set out the background some invertebrates used in pisciculture; earthworms, termites and maggots through their ecology, biology, system of production and their utility in pisciculture.
Keywords: Aquaculture; invertebrates; feed; termites; earthworm; maggot